The Effects of Solar Energy Curriculum Lesson Module on Senior Secondary School Physics Students’ Awareness of Air Pollution in Abuja, Nigeri - aliyu, aliyu yaya; Uwadileke Obi (CV Media Inti Teknologi, 2025)
Background of study: Air pollution is a critical global and local environmental challenge, particularly in urban centers such as Abuja, Nigeria. Despite its health and economic impacts, awareness among secondary school students remains limited. Integrating renewable energy education, especially solar energy, into the school curriculum is considered a promising strategy to enhance environmental literacy. Aims and scope of paper: This study investigates the effect of a solar energy curriculum module on improving senior secondary school physics students’ awareness of air pollution. It aims to determine baseline awareness, assess changes after the intervention, and examine the sustainability of awareness gains over time. Methods: A quasi-experimental pre-test/post-test design was employed with a sample of 423 physics students selected through Cochran’s formula and multistage sampling. Data were collected using a validated questionnaire, “Air Pollution and Solar Energy Knowledge and Attitudes Questionnaire (APSEK-AQ),” with a Cronbach’s alpha of 0.78. Descriptive statistics and paired t-tests were used to analyze data at a significance level of p < 0.05. Result: Findings revealed a significant improvement in awareness levels after the intervention (p < 0.001). Students with high awareness increased from 7.8% to 31.7%, while those with no awareness dropped from 29.6% to 9.9%. At a one-month follow-up, more than 55% of students retained moderate to high awareness levels, demonstrating sustained impact of the intervention. Conclusion: The solar energy curriculum module effectively enhanced students’ awareness of air pollution and supported knowledge retention. The study highlights the importance of integrating context-based renewable energy education into secondary curricula to promote environmental literacy and contribute to achieving SDG 4.7 and SDG 13.